Siglec-5 and Siglec-14 mediate the endocytosis of ADAMTS13. Issue 219 (November 2022) - Akiyama, Masashi; Eura, Yuka; Kokame, Koichi
Abstract: Background: The plasma metalloprotease ADAMTS13 regulates the thrombotic activity of the von Willebrand factor (VWF). ADAMTS13 is highly glycosylated and its carbohydrate chains are capped with sialic acid (SA). Thus, ADAMTS13 may interact with carbohydrate- and/or SA-binding plasma membrane receptors that are involved in the clearance of various plasma proteins. We have investigated ADAMTS13 endocytosis via Siglecs, which were originally identified as SA-binding immunoreceptor family proteins expressed on leukocytes and are also known as endocytic receptors. Materials and methods: Endocytic internalization of fluorescently labeled ADAMTS13 into HEK293 cells expressing Siglecs was examined via fluorescence microscopy. In vitro binding of ADAMTS13 to the extracellular region of Siglec-5 was examined. Plasma ADAMTS13 activity in human Siglec-5-expressing mice was measured. Results and conclusions: Siglec-5- and Siglec-14-expressing cells internalized not only full-length ADAMTS13 (FL) but also the truncated form (MDTCS) at least partly in an SA-independent manner. Replacement of the V-set domain of Siglec-14 with that of Siglec-3 abrogated the internalization of ADAMTS13. ADAMTS13 directly bound to the extracellular region of Siglec-5 in vitro. Expression of Siglec-5 in the mouse liver resulted in a significant decrease in plasma ADAMTS13 activity. These results suggest that Siglec-5 and Siglec-14, which have nearly identical ligand-binding domains, may contribute to the regulation of plasma ADAMTS13 levels as endocytic receptors for ADAMTS13. Highlights: ADAMTS13 was endocytosed by Siglec-5 and Siglec-14-expressing cells. The V-set domain of Siglec-5/14 was involved in ADAMTS13 endocytosis. ADAMTS13 bound to the extracellular region of Siglec-5 in vitro. Plasma ADAMTS13 activity was reduced by expression of Siglec-5 in mouse liver.